Unequal English Wealth since 1670 - Lindert, Peter H. (Journal of Political Economy, 1986)
New data on probated wealth, landownership, debts, and occupations extend our view of the distribution of English wealth back from 1911 to 1670. There were widening gaps in mean wealth between the top landed-plus-merchant classes and the middle classes across the Industrial Revolution century. Size distributions for individual assets also widened. So did those for income or total wealth (including human). But nonhuman net worth did not become more unequal because of important shifts in the land share. All inequality measures before 1914 exceeded all those since 1950. The estimates illuminate classical theories of distribution.